Vale Professor Hema Wijewardena: Quest for knowledge - Anura De Zoysa (Australasian Accounting, Business and Finance Journal, 2018)
In memory of the recent death of Professor Hema Wijewardena, accounting academic and pioneer of commerce education in Sri Lanka, we recognise his contribution to commerce education in Sri Lanka and Australia over four decades.
Keywords: Vale; Obituary; Hema Wijewardena; Quest for knowledge; Accounting; Sri Lanka